2014
DOI: 10.3109/00016489.2014.892212
|View full text |Cite
|
Sign up to set email alerts
|

Remote programming of MED-EL cochlear implants: users' and professionals' evaluation of the remote programming experience

Abstract: In all, 33 remote programming sessions were carried out, resulting in 99 completed questionnaires. The overwhelming majority of study participants responded positively to all aspects of remote programming. CI users were satisfied with the results in 96.9% of the programming sessions; 100% of participants would use remote programming again. Although technical problems were encountered, they did not cause the sessions to be considerably longer than face-to-face sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 12 publications
1
32
0
17
Order By: Relevance
“…This is likely due to the widespread use of personal technology such as cellular phones, tablets, and personal computers, which utilize webcams for video chatting (e.g., Skype, FaceTime, Google Chat). Responses to the questionnaire in the present study are similar to responses obtained in other reports (Hughes et al, 2012;Kuzovkov et al, 2014;Ramos et al, 2009;Wesarg et al, 2010), which generally show a positive attitude toward remote CI service delivery.…”
Section: Parent/caregiver Questionnairesupporting
confidence: 80%
See 4 more Smart Citations
“…This is likely due to the widespread use of personal technology such as cellular phones, tablets, and personal computers, which utilize webcams for video chatting (e.g., Skype, FaceTime, Google Chat). Responses to the questionnaire in the present study are similar to responses obtained in other reports (Hughes et al, 2012;Kuzovkov et al, 2014;Ramos et al, 2009;Wesarg et al, 2010), which generally show a positive attitude toward remote CI service delivery.…”
Section: Parent/caregiver Questionnairesupporting
confidence: 80%
“…For adult and adolescent recipients, several studies have shown equivalent outcomes in sound-processor programming ("map") levels between telepractice and in-person appointments (Eikelboom, Jayakody, Swanepoel, Chang, & Atlas, 2014;Hughes et al, 2012;Kuzovkov et al, 2014;McElveen et al, 2010;Ramos et al, 2009;Wesarg et al, 2010). In addition, audiologist and recipient feedback regarding telepractice has been positive, indicating that patients would take advantage of telepractice if it were routinely available (Hughes et al, 2012;Kuzovkov et al, 2014;Ramos et al, 2009;Wesarg et al, 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations